(untitled) (Research, Society and Development, 2021)
Purpose: Penile cancer has a high incidence in some developing countries and metastasis in lymph nodes in the inguinal chain is a major challenge in the treatment of this neoplasia. The aim of this study was to identify the prevalence of metastasis in inguinal lymph nodes and their associated factors in patients with penile cancer.Methods: A retrospective analysis was made of all consultations by adult males with regard to penile lesions at our institution. Metastasis in inguinal lymph nodes was the event of interest and was defined based on the presence of squamous cell carcinoma in inguinal lymph nodes which had been confirmed by anatomopathological examination. We performed bivariate logistic regression analysis and the magnitude of the associations was expressed by the Odds Ratio as an estimate of the relative risk with a 90% confidence interval.Results: A prevalence of 24% of metastases was found among the 179 analyzed cases of squamous cell carcinoma of the penis. The presence of palpable lymph nodes in the inguinal region at the time of diagnosis (p = 0.008) and abuse of alcohol (p = 0.07) were independent associated factors for the disease becoming more aggressive.Conclusions: Patients diagnosed with penile squamous cell carcinoma, who present palpable lymph nodes in the inguinal region during the clinical examination and those who drink alcohol, should be an early target for interventions in the uro-oncology services.